An updated review of mechanistic potentials of melatonin against cancer: pivotal roles in angiogenesis, apoptosis, autophagy, endoplasmic reticulum stress and oxidative stress - Saeed Mehrzadi; Mohammad Hossein Pourhanifeh; Alireza Mirzaei; Farid Moradian; Azam Hosseinzadeh (Cancer Cell International, 2021)
Abstract Cancers are serious life-threatening diseases which annually are responsible for millions of deaths across the world. Despite many developments in therapeutic approaches for affected individuals, the rate of morbidity and mortality is high. The survival rate and life quality of cancer patients is still low. In addition, the poor prognosis of patients and side effects of the present treatments underscores that finding novel and effective complementary and alternative therapies is a critical issue. Melatonin is a powerful anticancer agent and its efficiency has been widely documented up to now. Melatonin applies its anticancer abilities through affecting various mechanisms including angiogenesis, apoptosis, autophagy, endoplasmic reticulum stress and oxidative stress. Regarding the implication of mentioned cellular processes in cancer pathogenesis, we aimed to further evaluate the anticancer effects of melatonin via these mechanisms.